Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s10532-011-9531-8
|View full text |Cite
|
Sign up to set email alerts
|

Uranium reduction and microbial community development in response to stimulation with different electron donors

Abstract: Stimulating microbial reduction of soluble U(VI) to less soluble U(IV) shows promise as an in situ bioremediation strategy for uranium contaminated groundwater, but the optimal electron donors for promoting this process have yet to be identified. The purpose of this study was to better understand how the addition of various electron donors to uraniumcontaminated subsurface sediments affected U(VI) reduction and the composition of the microbial community. The simple electron donors, acetate or lactate, or the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 60 publications
(85 reference statements)
1
14
0
Order By: Relevance
“…However, under strongly alkaline conditions, negatively charged uranyl-carbonate complexes, like [UO 2 (CO 3 ) 2 ] 2Ϫ and [UO 2 (CO 3 ) 3 ] 4Ϫ , predominate (17)(18)(19). It is important to understand how these different U species interact with bacterial cellular surfaces, especially for designing biological wastewater treatment systems.…”
Section: (Oh)]mentioning
confidence: 99%
“…However, under strongly alkaline conditions, negatively charged uranyl-carbonate complexes, like [UO 2 (CO 3 ) 2 ] 2Ϫ and [UO 2 (CO 3 ) 3 ] 4Ϫ , predominate (17)(18)(19). It is important to understand how these different U species interact with bacterial cellular surfaces, especially for designing biological wastewater treatment systems.…”
Section: (Oh)]mentioning
confidence: 99%
“…The extent of U(VI) reduction was found to be higher with methanol than with glucose and much higher with glucose as compared to ethanol (Madden et al, 2009). Vegetable oil and HRC were more effective in stimulating U(VI) removal than acetate (Barlett et al, 2012a).…”
Section: Various Electron Donors Have Been Shown To Stimulate Bacterimentioning
confidence: 87%
“…Among them, acetate is the most common electron donor used in both laboratory and field experiments, followed by ethanol, lactate, and glucose (Francis et al, 1988;Finneran et al, 2002;Luo et al, 2007;Shelobolina et al, 2008;Barlett et al, 2012a). Other electron donors include benzoate, butyrate and butanol, and aromatic hydrocarbons such as toluene , hydrogen, formate, pyruvate, and fumarate (Finneran et al, 2002;Liu et al, 2002;Esteve-Núñez et al, 2004;Shelobolina et al, 2008;Marshall et al, 2009;Prakash et al, 2009;Junier et al, 2010).…”
Section: Various Electron Donors Have Been Shown To Stimulate Bacterimentioning
confidence: 99%
See 1 more Smart Citation
“…Recent investigations studied the formation of the biofilm by Shewanella Oneidensis MR-1 and found that the initial layer of the biofilm was produced by bacteria until the coverage of the surface and, consequently the formation of vertical towering biofilm structures (Thormann, Saville et al 2004). Furthermore, acetate and lactate have been reported to be less effective stimulants for U(VI) reduction, whereas more complex organic electron donors have been directly correlated to the ability of DMRB to reduce U(VI) (Barlett, Moon et al 2012). …”
Section: Sem-eds Analysis and Speciation Studiesmentioning
confidence: 99%